Salicylic acid foliar application increases biomass, nutrient assimilation, primary metabolites and essential oil content in Achillea millefolium L - Gorni, Pedro Henrique; Pacheco, Ana Cláudia; Moro, Adriana Lima; Silva, Jonathan Fogaça Albuquerque; Moreli, Ronaldo Rossetti; de Miranda, Giovani Rodrigues; Pelegrini, Juler Martins; Spera, Kamille Daleck [UNESP]; Bronzel, João Luiz [UNESP]; da Silva, Regildo Márcio Gonçalves [UNESP] (Elsevier, 2020)
Salicylic acid (SA) is a phenolic phytohormone that acts in different physiological plant processes and is considered an efficient elicitor in the production of secondary metabolites, including essential oils. The effects of SA on biomass production, primary metabolites contents and nutrients in leaves of Achillea millefolium L. plants were evaluated. Additionally, the effect of SA on the quantity and quality of essential oil was evaluated. The experiments were carried out under field conditions in two consecutive seasons (2016 and 2017), with SA foliar applications at a dose of 1.0 mmol L-1 in different periods (20, 60 and 100 days after planting - DAP and at 100 DAP for three consecutive days) with water treated plants as control. Plants treated with SA showed higher dry weight values (leaf, root and total) and photosynthetic pigment contents. The positive effects of SA on the primary plant metabolism were evidenced by the higher concentrations of total sugars, proteins and amino acids in both application periods and years of cultivation. The levels of macronutrients in the leaves were also increased compared to the controls. SA applications resulted in higher content and yield of essential oil. The qualitative analysis of the essential oil showed the predominant presence of volatile compound chamazulene. Our results have demonstrated that the application of 1.0 mmol L-1 of SA at 100 DAP induced a series of coordinated metabolic changes that resulted in increases in yield and essential oil content in A. millefolium, which makes the aerial application of this elicitor a promising approach for its use in plants grown under field conditions.
Keywords: chamazulene; eliciting activity; GC-MS; productivity